Effectiveness of Atraumatic Needle to Avoid Post-Dural Puncture Headache - Yaseen, Talha; Rizvi, Syed Ali Mazhar; Malik, Usman Eijaz; Khan, Abid; Mahmood, Khalid; tarat, Humayun Munir (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine occurrence of headache after a dural puncture using an atraumatic needle. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Anesthesia, Combined Military Hospital, Rawalpindi Pakistan, from Apr to Sep 2021. Methodology: A total of 336 patients were divided into two groups of 168 patients each, after obtaining institutional approval and informed consent from patients. Female patients, of reproductive age group, who were scheduled to receive subarachnoid block before c-section, were included in the study. We compared the usage of a traumatic needle (25 gauge) compared to atraumatic (25 gauge) in causing post-lumbar puncture (LP) headache. Results: Post-LP headache occurred in 7.1% of the patients assigned to the atraumatic needle and 32% of the patients assigned to the traumatic needle, which was found to be significant (p=0.001). Conclusion: We found that usage of atraumatic needles led to a reduction in the occurrence of headaches during lumbar puncture.